Inflammatory Myofibroblastic Bladder Tumor in a Patient with Wolf-Hirschhorn Syndrome. (18th August 2013) - Marte, Antonio; Indolfi, Paolo; Ficociello, Carmine; Russo, Daniela; Oreste, Matilde; Bottigliero, Gaetano; Gualdiero, Giovanna; Barone, Ciro; Vigliar, Elena; Indolfi, Cristiana; Casale, Fiorina
Abstract : Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm described in several tissues and organs including genitourinary system, lung, head, and neck. The etiology of IMT is contentious, and whether it is a postinflammatory process or a true neoplasm remains controversial. To our knowledge, we report the first reported case of IMT of urinary bladder in a pediatric patient with Wolf-Hirschhorn (WHS). We also review the literature about patients with associated neoplasia.